The use of impulse ventilation to control pollution in underground car parks - Viegas, J. (2009)
The ventilation of underground car parks is important to avoid health problems with the inhalation of combustion products released by car engines, in special CO (that is commonly used as the indicator of indoor air quality). In last years, a new mechanical ventilation system appeared, based on the use of axial ventilators (jet fans) suspended under the car park ceiling. In this paper the flow generated by jet fans and their effects on the pollutants are studied. It is concluded that jet fans may have a pumping effect entraining the surrounding contaminated air into the jet. In this way jet fans are able to restrict the dispersion of the contaminants, provided that the exhaust flow rate from the car park is not lower than the jet flow rate. Impulse ventilation may also provide fast dilution of the local pollution peaks, but in this case the removal efficiency will be low. This paper also suggests criteria to define the distance between jet fans.